Measurement of tensor analyzing power T20 and T21 in elastic electron-deuteron scattering; Physical Review Letters; Vol. 90, № 7 - Nikolenko D. M.; Arenhovel H.; Barkov L. M.; Belostotsky S. I.; Dmitriev V. F.; Dyug M. V.; Gilrnan R.; Holt R. J.; Isaeva L. G.; de Jager C. W.; Kinney E. R.; Kowalczyk R. S.; et al. (2003, 2003)
The tensor analyzing power components T20 and T21 have been measured in elastic electron-deuteron scattering at the 2 GeV electron storage ring VEPP-3, Novosibirsk, in a four-momentum transfer range from 8.4 to 21.6  fm-2. A new polarized internal gas target with an intense cryogenic atomic beam source was used. The new data determine the deuteron form factors GC and GQ in an important range of momentum transfer where the first node of the deuteron monopole charge form factor is located. The new results are compared with previous data and with some theoretical predictions